Kesulitan Belajar Mata Kuliah Kemuhammadiyahan I Bagi Mahasiswa Non Muslim di Program Studi PGSD Universitas Muhammadiyah Palangka Raya - Yati, Fella (Jurnal Studi Agama dan Masyarakat, 2015)
The problems of the study in this research were 1) the studentsâ difficulty in learning about the course of Kemuhammadiyahan I and 2) the internal and external factors that caused the studentsâ difficulty in learning for non-Muslim students for Therefore, the purpose of this study was 1) to describe the difficulty in learning that was faced by non-Muslim students in attending Kemuhammadiyahan I at PGSD Study Program, UMP, and 2) to describe the internal and external factors that caused the non-Muslim studentsâ difficulty in attending Kemuhammadiyahan I at PGSD Study Program, UMP. The result of the study showed that (a) there was no difficulty in learning found from non-Muslim students in Kemuhammadiyahan I, this result was based on the score of Kemuhammadiyahan I from the total of 5 students who became the subject of the study. (b) Having reviewed from the internal and external factors, from 16 non-Muslim students who took Kemuhammadiyahan I, there were 5 students who were chosen as the subjects. Concerning the internal factor, it was due to the studentsâ lack of motivation, interest, and also attention to the course. Â The results showedÂ  it does not occur non-Muslim students learning difficulties in the course Kemuhammadiyahan I